Pendampingan Pembuatan Media Pembelajaran Kubus sebagai Alat Permainan Ular Tangga - Asep Saeful Rohman; Yeni Sulaeman; Linda; Ira Asyura; Asep Saefullah Kamali (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2023)
Assistance in making cube learning media as a tool for playing snakes and ladders is the background to the problems at SDN Mekarsari 2 due to the lack of student interest in mathematics. Geometric materials at the basic education level especially need application and are not easily understood by theory alone. This writing aims to provide a better understanding of geometric material and increase student motivation in participating in mathematics through the cube learning media as a tool for playing snakes and ladders. The subjects of this study were 32 students in class V, totaling 32 students at SDN Mekarsari 2. The assistance was carried out through several methods, including observation through interviews with students, socialization, program implementation in the form of making media cubes and practice, namely the application of cubes as dice in the snake games ladder. After four days of mentoring, starting from the observation stage to the practice of the snakes and ladders game, the result was an increase in students' motivation to take part in learning, as well as being able to solve problems and questions about cube building materials as well as mathematical operations.